Volume 3: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration 2015
DOI: 10.1115/gt2015-43736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Air Filtration Options for an Industrial Gas Turbine

Abstract: Gas turbines ingest large quantities of air during operation. As a result, large quantities of foreign particles ranging in size from smoke (0.01 to 1.0 micron) to pollen (10 micron) enter the unit and can contribute to both fouling and erosion depending on particle size. Fouling and erosion both lead to reductions in unit output and efficiency resulting in increased operational cost. Operators have historically combatted fouling through a combination of online water washes, more effective off-line water washe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Looking at the data, the pressure ratio values appear randomly dispersed and very similar to the data reported in the literature related to on-field detections [7,8]. The linear trend used for interpolating the data is adopted according to the literature [13] and allows the definition of the compressor performance drop.…”
Section: Performancementioning
confidence: 57%
See 2 more Smart Citations
“…Looking at the data, the pressure ratio values appear randomly dispersed and very similar to the data reported in the literature related to on-field detections [7,8]. The linear trend used for interpolating the data is adopted according to the literature [13] and allows the definition of the compressor performance drop.…”
Section: Performancementioning
confidence: 57%
“…This technique is adopted mainly for studying the deposition phenomenon of cold and hot gas turbine sections [2 -4]. For this reason, the exposure time adopted in the present investigation is 30 min that covers about 500 operating hours of an actual installation [8].…”
Section: Compressor Fouling Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of natural and/or artificial micro-sized particles, together with the air humidity, are those of the most critical variables on the fouling rate [7]. Literature data have revealed that the fouling issue affects the unit performance despite the presence of filtration systems [8,9] and, only with a periodic (frequent) online washing operation [5,10,11], the reliability of the engine remains acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…These applica- 103 tions are characterized by the contemporary presence of erosion 104 and fouling phenomena [6][7][8]. 105 One of the first reports on gas turbine operation in a power plant 106 can be found in Carameros's study [9]. This is a summary of El 107 Paso Natural Gas Company's operating experience, covering the 108 design and operating problems encountered during the period 109 between September 1952 and January 1956.…”
Section: Introductionmentioning
confidence: 99%